Effect of fat content and grinding level of cocoa nibs on physicochemical characteristics of espresso cocoa - Md Dali, Aisyah Zafirah; Karim, Roselina; Selamat, Jinap; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Grinding is an important factor in espresso coffee preparation and the optimal grinding level is needed to improve its characteristics. However, a problem arises where ground cocoa nibs change from solid to fluid mass at finer level due to high fat content (52%) in the cocoa bean. Thus, the aim of this study was to determine the effect of fat in Ivory Coast cocoa nibs and grinding level on particle size and the physicochemical characteristics including viscosity (mPa), pH, foam index (%), density (g/mL), total solid (mg/mL) and extraction (%) of espresso cocoa (ECOC). Solvent extraction was used to produce defatted cocoa nibs (40%, 34% and 20%) and was ground at four different grinding levels (i.e., 10, 30, 50 and 70) to extract a cup of ECOC using espresso machine. The grinding level 70 (1665.0±28.30 μm) contributed to significantly (p<0.05) coarsest particle size compared to the smallest grinding level 10 (340.0±21.20 μm). However, only grinding level 50 and 70 were selected as they contributed a good extraction of ECOC with targeted volume of 40 mL. Overall, ECOC with fat content of 20% at grinding level 50 produced significantly (p<0.05) the most viscous (5.63 mPa), the highest foam index (10.83%) the highest density (1.00 g/mL), the highest total solid content (24.36 mg/ml), and the highest extraction value (10.37%) of ECOC compared with another type of ECOC and control. This study is important to develop high quality ECOC as another alternative beverage for cocoa.